BUDAYA VIRAL DAN FOMO SEBAGAI PEMICU CYBERBULLYING: URGENSI TABAYYUN DAN ETIKA BERMEDIA SOSIAL DALAM PENDIDIKAN ISLAM - Inten Medita Oktaria; Azizah Nur Aini; Firda Hafiz Fadillah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the relationship between viral culture and the phenomenon of Fear of Missing Out (FoMO) with the tendency of cyberbullying behavior on social media, as well as to examine the urgency of implementing the principle of tabayyun and ethical communication from the perspective of Islamic education. This research uses a quantitative approach with a descriptive method through questionnaires distributed to 85 respondents consisting of students, university students, and workers. The findings show that most respondents have high awareness of social media ethics and the dangers of cyberbullying, yet they are not fully consistent in practice. Viral culture and FoMO significantly influence user behavior, particularly in encouraging impulsive responses, trend-following tendencies, and lack of consideration in commenting. These findings are in line with social learning theory and media theory, which explain that digital behavior is shaped by environmental exposure and media influence. Furthermore, the Islamic principle of tabayyun, which emphasizes information verification, is highly relevant to modern digital literacy practices such as fact-checking and critical thinking. Therefore, integrating the values of tabayyun and ethical communication in Islamic education is essential to develop responsible, critical, and ethical social media users.